2010
DOI: 10.1590/s0037-86822010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of measles IgM-seropositive cases of febrile rash illnesses in the absence of documented measles virus transmission, State of São Paulo, Brazil, 2000-2004

Abstract: INTRODUCTION: To review measles IgM-positive cases of febrile rash illnesses in the State of São Paulo, Brazil, over the five-year period following interruption of measles virus transmission. METHODS: We reviewed 463 measles IgM-positive cases of febrile rash illness in the State of São Paulo, from 2000 to 2004. Individuals vaccinated against measles < 56 days prior to specimen collection were considered to be exposed to the vaccine. Serum from the acute and convalescent phases was tested for evidence of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Others have described the occurrence of false-positive measles and rubella IgM test results, including a case report of a patient who was diagnosed with parvovirus infection after initially testing positive for measles IgM [ 34 ], as well as reports of false-positive IgM results that were resolved with additional IgG testing [ 35 , 36 ]. However, to our knowledge ours is the first study that used confirmed cases of measles and rubella investigated by public health authorities as the gold standard to calculate IgM test performance.…”
Section: Discussionmentioning
confidence: 99%
“…Others have described the occurrence of false-positive measles and rubella IgM test results, including a case report of a patient who was diagnosed with parvovirus infection after initially testing positive for measles IgM [ 34 ], as well as reports of false-positive IgM results that were resolved with additional IgG testing [ 35 , 36 ]. However, to our knowledge ours is the first study that used confirmed cases of measles and rubella investigated by public health authorities as the gold standard to calculate IgM test performance.…”
Section: Discussionmentioning
confidence: 99%
“…Their results are different from ours. Our younger children had more coryza, Koplik's spot, and other complications, albeit fewer instances of cough, conjunctivitis, and hyperpigmentation, as showed in the Table 3. A study by Ciccone et al with 463 participants found the clinical features of measles patients as follows: fever (85%), rash (97%), cough (46%), coryza (48%), and conjunctivitis (17%) [57]. In the study by Chan et al 165 subjects were recruited, with the following proportions of clinical features: fever (100%), rash (100%), cough (96.4%), coryza (98.25%), conjunctivitis (58.2%), and Koplik's spot (75.2%) [56].…”
Section: Discussionmentioning
confidence: 99%
“…As countries move from rubella control to elimination, the implementation of vaccination has directed a significant decrease in rubella incidence, resulting in a reduction in the positive predictive value of IgM assay [Medici et al, , Ciccone et al, , Wandinger et al, ]. This reduction has led to a significant risk of false‐positive results [Best ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few articles to differentiate the etiology of rash in rubella‐like illnesses [Davidkin et al, , Davidkin et al, , Ciccone et al, ]. However, limited studies have been conducted on clarifying the source of IgM positivity in these cases.…”
Section: Discussionmentioning
confidence: 99%